الادوات الحديثة للاستعلام الاقتصادي ودورها في الرفع من تنافسية المؤسسة الاقتصادية - شريط, حسان; بوخاري, راضية (جامعة الوادي - University of Eloued, 2024)
This study aims to examine and clarify the reality of using economic intelligence tools within the COGRAL company. In today's ever-changing environment, economic intelligence tools, including strategic vigilance, cybersecurity, and influence, have become more crucial than ever for companies that want to stay competitive. These tools enable them to seize opportunities, anticipate risks, protect sensitive information, and influence decision-making.A descriptive approach and interviews were employed for data collection. The results revealed that COGRAL company managers often do not realize the significant role that economic intelligence tools play in enhancing the company's competitiveness. Therefore, awareness of economic intelligence within the company is limited
Modern tools for economic intelligence and their role in raising the competitiveness of the economic enterprise
مقال
Keywords: أدوات الاستعلام الاقتصادي، تنافسية المؤسسة، مؤسسة COGRAL، اليقظة الاستراتيجية، الأمن الالكتروني; :Economic Intelligence Tools, Competitiveness, COGRAL Company, Strategic Vigilance, Cybersecurity.